Performance Analysis of Apron Movement Control Officers in Supervising Vehicle Traffic to Achieve 3S+1C at the Apron of Juanda International Airport, Surabaya - Jagadhika Alfitra Ageng; Hodi Hodi (CV. Rayyan Dwi Bharata, 2023)
Juanda International Airport in Surabaya is the largest airport in East Java serving domestic and international flights. How is the performance of Apron Movement Control (AMC) officers in supervising vehicle traffic in order to achieve 3S + 1C at Juanda International Airport What are the efforts of Apron Movement Control (AMC) officers in supervising vehicle traffic in order to achieve 3S + 1C at Juanda International Airport The performance of Apron Movement Control (AMC) officers to supervise vehicle traffic in order to achieve 3S + 1C at Juanda International Airport. The performance of Apron Movement Control (AMC) officers in supervising vehicle traffic in order to achieve 3S + 1C at Juanda International Airport. This research was conducted using qualitative methods. by collecting primary data, secondary. The primary data in this study used interviews, observation, and data collection in the form of pictures or documentation during the activity. for secondary data in the form of data documentation of vehicle traffic control activities. After being collected, data processing was carried out using triangulation techniques. The results of this study are that Apron Movement Control Officers must carry out strict and optimal supervision of vehicle traffic by conducting Apron Patrols, Random Checks and periodic inspections of Officers, Operators, vehicles and facilities. As well as carrying out work in accordance with SOPs and other applicable rules so that operations run smoothly in accordance with regulations and perform optimal service and be responsive to conditions or potential that may occur.